Pattern of Noise Induced Hearing Loss and its Relation with Duration of Exposure in Traffic Police Personnel - Gupta, Mrityunjay; Khajuria, Vijay; Manhas, Monica; Gupta, Kasturi Lal; Singh, Onkar (Indian Journal of Community Health, 2015)
Background: Occupational noise exposure is a major and preventable cause of hearing loss. Traffic policemen are constantly exposed to noise pollution. Noise induced hearing loss (NIHL) denotes a selective 4000 Hz hearing loss (unilateral or bilateral). Objective: To assess the prevalence pattern of NIHL and its relation with duration of exposure to noise in traffic policemen. Material and methods: Otoscopy, tuning fork tests and Pure Tone Audiometry (PTA) were performed in 150 apparently healthy police personnel. Results: Rinne’s and Weber’s test were normal in all the subjects. Schwabach’s test showed normal bone conduction in normal subjects as well as those with NIHL. PTA revealed that 33 (22% of sample) subjects were suffering from NIHL; 8 (5.3%) had sensorineural hearing loss whereas 109 (72.7%) performed normally in the test. None of the subjects with sensorineural hearing loss showed the characteristic notch at 4 kHz. Majority of the subjects (69.7%) with NIHL had mild to moderate grades of hearing loss in both ears. No subject had profound hearing loss. Significant association was observed between NIHL and duration of exposure. Steps need to be taken at the level of employers as well as individuals to counter occupational noise threat.